The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1590/s0074-02761984000400012
|View full text |Cite
|
Sign up to set email alerts
|

Biomphalaria Tenagophila Guaibensis ssp. n. from Southern Brazil and Uruguay (pulmonata: Planorbidae). I. Morphology

Abstract: A new subspecies of planorbid snail, biomphalaria tenagophila guaibensis, is described. It has been found along the coastal belt of the Brazilian state of rio grande do Sul and the middle part of Uruguay, from Porto Alegre to Mercedes. It differs from the nominate subspecies, Biomphalaria tenagophila tenagophila, in the appearance of the penial complex (prepuce longer and proportionally slenderer in B. t. guaibensis, shorter and proportionally stouter in b. t. tenagophila), in the ratio between the lengths of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
34
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 0 publications
3
34
0
2
Order By: Relevance
“…In some B. t. guaibensis specimens from different populations than those analysed in our study, a dark pigmentation was observed on the renal tube, which had not been reported by Paraense (1984). Among the planorbid species described in Brazil, the only species known to have a pigmented renal tube is B. glabrata, the main S. mansoni transmitter species in Brazil (Paraense 1975).…”
supporting
confidence: 49%
See 3 more Smart Citations
“…In some B. t. guaibensis specimens from different populations than those analysed in our study, a dark pigmentation was observed on the renal tube, which had not been reported by Paraense (1984). Among the planorbid species described in Brazil, the only species known to have a pigmented renal tube is B. glabrata, the main S. mansoni transmitter species in Brazil (Paraense 1975).…”
supporting
confidence: 49%
“…Although a survey by Teles et al (1991) showed no evidence of such species in RS, Paraense (1984) had reported its occurrence in Arroio Grande, Jaguarão and Pelotas (RS).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…
Biomphalaria tenagophila is a planorbid with a wide distribution in South America (Paraense 1984), and has epidemiological importance, since this species maintains the cycle of the trematode Schistosoma mansoni in some areas in Brazil. In spite of its dominance in some areas, B. tenagophila is found in the nature with low rates of infection, however, it is responsible for the majority of the autochthonous cases of schistosomiasis in the state of São Paulo, as well as for the foci of the disease in the states of Minas Gerais and Santa Catarina (Paraense 1986).
…”
mentioning
confidence: 99%